Influence of stabilization splint thickness on temporomandibular disorders - Bilir, Halenur; Kurt, Hanefi (Quintessence Publishing Co, Inc, 2022)
Purpose: To assess the effect of stabilization splint (SS) thickness on temporomandibular disorders (TMDs). Materials and Methods: Participants were selected from patients who applied to the clinic with a complaint of temporomandibular disorders (TMDs). Symptoms were evaluated with the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD). Regarding the treatment plan, patients were divided into two groups: the 2-mm-thick splint group (2-mm TSG) and the 4-mm-thick splint group (4-mm TSG). They used SSs at night (8 hours) and were recalled 1, 2, 3, and 6 months after splint insertion. At the end of the study, 72 patients (2-mm TSG = 39, 4-mm TSG = 33) had completed the 6-month follow-up. The SPSS program was used for statistical analysis. The results of the analysis were evaluated at a significance level of .05. Results: Pain in the muscles decreased significantly in the muscle disorders and combined groups (both 2- and 4-mm TSG) after 6 months of treatment (P < .05). In the combined group, TMJ sounds significantly decreased after 6 months of treatment, and there was a statistically significant difference between the 2-mm TSG and the 4-mm TSG (P = .045). Also, in the combined group, maximum unassisted opening (MUO) values of patients treated with 2-mm-thick splints decreased after 6 months of treatment (P = .022). Conclusion: Both 2-mm-thick and 4-mm-thick splints were effective in the treatment of muscle disorders and disc displacements, especially in muscle-related pain and TMJ sound symptoms.
Keywords: Stabilization Splint Thickness; Temporomandibular Disorders; Influence